Developing a proficiency test of academic english in the Indonesian higher education context - Didi Sukyadi; Fuad Abdul Hamied; Ika Damayanti; Ari Arifin Danuwijaya; Lukman Hakim; Firly Asyifa (Jurnal Cakrawala Pendidikan, 2026)
Standardized tests remain crucial for students whose first language is not English in today’s globalized world, despite ongoing debates about their suitability. The purpose of this research is to develop an academic English proficiency test for higher education in Indonesia. The data were derived from a needs analysis conducted through focus group discussions (FGDs) and a pre-survey for the existing academic English proficiency test, followed by a test design process: creating a test blueprint and developing question items, and a second survey following a trial test with 538 test takers. The findings indicate that adjustments were required to the test format and duration, a basis for developing a new test format. Additionally, students reported a preference for computer-based tests. During the test design process, the research team revised the test, retained the test objectives, and modified the item test types. Lastly, post-test feedback and item analysis indicated an imbalance in item difficulty in the Structure and Written Expression section, while the Academic Listening and Academic Reading sections demonstrated relatively balanced difficulty levels. Overall, the findings of this research indicate a desire to revisit and refine the existing test to better meet students’ needs while maintaining its objectives.